Careful how you hold me an insight into caring for laboratory animals. - University of Melbourne. Multimedia Education Unit. (Parkville, Vic. : Multimedia Education Unit, University of Melbourne, 1999)
A multimedia program for investigators, honours and postgraduate students, animal technicians and others new to the field of laboratory animal science and animal welfare, a resource for collective use or self paced learning.
System requirements: Intel Pentium processor, 75MHz or faster (Pentium 133MHz recommended); 16 MB RAM (32MB recommended); Windows 95, Windows 98 or Windows NT 4.0; Quicktime 3.0 or higher (installer included)
System requirements: any power Macintosh; 16MB of RAM (32MB recommended); Quicktime 3.0 or higher (installer included).
Digital content preserved
Keywords: Laboratory animals -- Interactive multimedia; Laboratory animals -- Study and teaching (Higher)